Significados do corpo no trabalho em indivíduos com diagnóstico de ler - Dale, Alana Pires [UNESP] (2015)
The constant appearance of sick workers reinforces the need for studies that address aspects of daily life in the work environment, in particular, the precarious working conditions, the introduction of new technologies, methods of organization and management of production processes. Among the most prevalent occupational diseases are the Repetitive Strain Injury (RSI) and Work-Related Musculoskeletal Disorders (WRMD), which are directly related to the organization of the work that ignores the limits of the body and the uniqueness of each individual worker. The main focus of this study was to investigate the significance of the body at work in individuals diagnosed with RSI and WRMD. To achieve the proposed objective, a case study was held in a qualitative approach, which is based in the sociohistorical theory of psychology, conducted by the conceptions of Leontiev and Vigotski, in search of the meanings attributed by the interviewed individuals. The means used to achieve the data was through individual open interviews with nine subjects whom had been diagnosed with RSI/WRMD and were accompanied at the Worker's Health Reference Center (WHRC) in Botucatu. From the collected information, three meaning cores have been revealed: Need to work: the body in motion; Body submission: lack of autonomy/power; and Prevented body: I caught, I stopped in my life. In addition to these, meanings and explanatory material have composed the illustrator scheme of results. The phrase that best defines the whole process of health/disease measured in the interviews according to the scenario reported by the individuals is The extravagance of working sick, and the product of this, is an Uncertain Future, replete with physical and mental suffering